The heart frequency and its variability in hypertensive patients considering A/B type of behaviour and eight basic emotions and levels of anger expression - Kožul, Karlo, liječnik (Array, 2009)
Abstract: The aim of this paper was to comparation between autonomic regulation of the heart rate and it’s variability within 100 essential hypertensive patients and 100 examinees in healthy control group. Essential hypertensive patients had significantly shorter average RR interval, that is, faster heart frequency then the control group. Average variability of the heart frequency was statisticaly considerably lower in hypertensive than in the healthy control group. Sistolic blood pressure, diastolic blood pressure, duration of hypertension, levels have considerate total influence on heart frequency and it’s variability during calm and during deep breathing. The most distinctive negative connection was found between variability of the heart frequency and duration of hypertension. The type A behaviour within hypertensive patients and the control group was more common then type B. In the hypertensive group, total influence of all independent Bortner’s variables on to variability of the heart frequency during calm breathing was statisticaly important. Within hypertensive patients and the control group, the heart frequency and it’s variability were connected with eight basic emotions. In the group of hypertensive patients variability of the heart frequency is significantly positively connected with emotional dimension »Incorporation«, but negatively with emotional dimensions »Protection«, »Rejection« and »Reproduction«. Our data showes that patients with long-term hypertension have increased heart frequency and reduced variability of the heart frequency, which are well-known risk factors for increased cardial mortality